The Role of Environmental Awareness in Shaping Residents’ Trip Lengths in Ogun State: A Sustainable Transportation Perspective - O, Gbadebo S.; O, Ogundele E. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines the role of environmental awareness in shaping residents' trip lengths in Ogun State, focusing on sustainable transportation perspectives. The research investigates intra-urban variations in trip lengths across different spatial structures: traditional, transitional, and suburban zones. Utilizing a descriptive and analytical approach, data were collected through surveys targeting 362 residents. Based on the findings, Females generated more trips (58.4% of total trips). Residents aged 30-44 made the most trips (average daily: 234.7). Individuals with ND/HND qualifications made the most trips (1,331 weekly). Households earning ₦60,000 - ₦120,000 made the highest number of trips (1,341 weekly). The findings reveal that about 44.1% of the residents in traditional zones predominantly undertake shorter trips (5.1-10 km), while about 23.6% of the respondents in suburban zones show a higher frequency of longer trips (above 20 km). Factors influencing travel behavior include socioeconomic characteristics, modal preferences, and environmental awareness. The study underscores the necessity for tailored urban planning and transportation policies that consider the unique attributes of each zone to promote sustainable travel behaviors.